MENCARI MODEL DESAIN KARAKTER DAN VISUALISASI PENOKOHAN DISC TEAM DALAM PEMBUATAN KOMIK - Joy Christy Fidelin Nicolay; Marina Wardaya (Universitas Ciputra Surabaya, 2021)
This design is made with the purpose of answering the problem that DISC Team is facing about product development. DISC Team is a series of short comics that has4 main characters that are inspired by the DISC personality trait. This comic tells the story of their daily lives and how they face problems according to the DISC personality trait. DISC Team has a target market that consists of young adults age from 15-25 years old who has an interest in reading comics and has the drive to learn about personality and how to face them. But after doing a survey with the target market and interviewed the extreme and expert users, there are problems that DISC Team is facing. These problems are the lack of interaction and knowledge about the presence of DISC Team, so further product development is needed. And because of that, the writer has a come up with a solution by changing the comic design. The research method that is used for this Final Project is literature study from sources like books, scientific journals and online articles. After the literature studies, the results are the designs for comic and its’ characters. Keywords: Product development, Comic, DISC personality